2007
DOI: 10.3409/173491607780006362
|View full text |Cite
|
Sign up to set email alerts
|

Laying Characteristics of One- and Two-year Old Pheasants (Phasianus colchicus, L.)

Abstract: The aim of the study was to assess laying traits, the weight of eggs and characters of the laying rhythm of pheasants in the first and second years of reproduction. Pheasants (10 cockerels and 50 hens) were kept in aviaries. Daily, individual control of laying was performed beginning with the day of the first laying and ending with the last egg. The following parameters were evaluated: age at first laying, length of the laying period, number of laid eggs and the average weight of the egg in the 8 th week of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…The lowest average values of the total erythrocyte count (2.66 ± 0.09 10 12 /L) and haemoglobin content (108.0 ± 2.9 g/L) were determined in week 6 of laying, which is roughly the period when the rate of laying of the common pheasant hen reaches its maximum, although the academic sources differ from this figure (e.g., Gibes et al [28], Woodard and Snyder [29], and Krystianiak et al [30]). A drop in the total number of erythrocytes ( P < 0.001) and haemoglobin ( P = 0.0356) in week 6 was followed by a significant increase in both indicators ( P < 0.001) in week 12.…”
Section: Resultsmentioning
confidence: 99%
“…The lowest average values of the total erythrocyte count (2.66 ± 0.09 10 12 /L) and haemoglobin content (108.0 ± 2.9 g/L) were determined in week 6 of laying, which is roughly the period when the rate of laying of the common pheasant hen reaches its maximum, although the academic sources differ from this figure (e.g., Gibes et al [28], Woodard and Snyder [29], and Krystianiak et al [30]). A drop in the total number of erythrocytes ( P < 0.001) and haemoglobin ( P = 0.0356) in week 6 was followed by a significant increase in both indicators ( P < 0.001) in week 12.…”
Section: Resultsmentioning
confidence: 99%
“…The pheasant production model (Delacour, 1959;Fol, 1961;Béjar, 1995;Canning, 2005;García Martín, 2005;Torres et al, 1995;Krystianiak et al, 2007) is partly similar to other game birds, such as partridges and quails. In complete-cycle farms, breeding pheasants with ages usually ranging from one to four (in some cases, up to seven) years old, are kept, frequently outdoors, in pens in harems or in colonies (in both cases, in a sex ratio of 1:5 to 1:7 male-to-females).…”
Section: Introductionmentioning
confidence: 99%
“…Another hypothesis may be to lay eggs in aviaries (environment very close to natural) in a broodable number, despite the gradual, daily pick-up. This is evidenced, among others, by Krystianiak et al (2007). The authors observed that pheasant hens in aviaries had average number of eggs in one clutch between 3 and 13.5.…”
Section: Discussionmentioning
confidence: 79%
“…Kuzniacka et al (2005) also reported a high laying rate of pheasants at the peak of production. The fact that the reproductive performance of this species can vary was confirmed by Krystianiak et al (2007). The authors found that the highest egg laying value was obtained between weeks 3-9 of egg production and in this period, this value fluctuated around 70%.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation